Transparency of the municipal public management: a study from the homepages of the large Brazilian municipalities - Cláudia Ferreira Cruz; Aracéli Cristina de Sousa Ferreira; Lino Martins da Silva; Marcelo Álvaro da Silva Macedo (Revista de Administração Pública, 2012)
This study attempts to check the transparency level of information in public administration published in the homepages of 96 municipalities included among the 100 most populous in Brazil and what characteristics and socioeconomic indicators of the municipalities can contribute to explain the level of transparency observed. The level of transparency in public administration was established from a research model called Transparency Index Municipal Public Management (ITGP-M) constructed based on international codes of good governance and transparency, the Brazilian legislation and the experiences of previous studies of similar nature conducted in Brazil and abroad. The empirical evidence point to low levels of transparency, incompatible with the level of socioeconomic development of municipalities. Moreover, we can conclude that, overall, there is an association between the socioeconomic conditions of the municipalities and the levels of transparency in the disclosure of information about public administration observed in sites of large municipalities as in this study.